ANALISIS PERTIMBANGAN MAHKAMAH AGUNG DALAM MENGKABULKAN KASASI PENUNTUT UMUM TERHADAP KESALAHAN JUDEX FACTIE - Bagas Prasetya Faliquzzaman; Muthia Sakti (Verstek, 2023)
Abstract: This study aims to analyze the consideration of the supreme court regarding the judex factie error in deciding that corruption was acquitted (Study of Supreme Court Decision Number 2407/K/Pid.Sus/2020). This type of normative research is prescriptive with a case approach. The research legal materials used are primary and secondary legal materials with library research collection techniques. This research shows that the consideration of the Supreme Court in decision Number 2407K/Pid.Sus/2020 is in accordance with Article 253 paragraph (1) of the Criminal Procedure Code because judex factie in this case the Decision of the Makassar High Court does not apply the law as it should. Keywords: Supreme Court, Judex Factie, Free Verdic